2010
DOI: 10.1038/labinvest.2010.123
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer cells are associated with apoptosis, inflammation and fibrotic effects in hepatic fibrosis in rats

Abstract: Hepatocellular apoptosis, hepatic inflammation, and fibrosis are prominent features in chronic liver diseases. However, the linkage among these processes remains mechanistically unclear. In this study, we examined the apoptosis and activation of Kupffer cells (KCs) as well as their pathophysiological involvement in liver fibrosis process. Hepatic fibrosis was induced in rats by dimethylnitrosamine (DMN) or carbon tetrachloride (CCl4) treatment. KCs were isolated from normal rats and incubated with lipopolysacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(117 citation statements)
references
References 32 publications
6
110
0
1
Order By: Relevance
“…There is overwhelming evidence that activated HSCs are the major producers of the fibrotic matrix (1-3). TGF-␤ is the key cytokine that mediates HSC activation, but the current model of TGF-␤-dependent HSC activation does not account for the contribution of inflammatory mediators to hepatic fibrogenesis (6), and extensive studies are aimed to establish a mechanistic link between inflammation and fibrosis in chronic liver disease (6,18). We have shown previously that BAMBI links inflammation and liver fibrosis via TLR4-dependent modification of TGF-␤ signaling in HSC.…”
Section: Discussionmentioning
confidence: 99%
“…There is overwhelming evidence that activated HSCs are the major producers of the fibrotic matrix (1-3). TGF-␤ is the key cytokine that mediates HSC activation, but the current model of TGF-␤-dependent HSC activation does not account for the contribution of inflammatory mediators to hepatic fibrogenesis (6), and extensive studies are aimed to establish a mechanistic link between inflammation and fibrosis in chronic liver disease (6,18). We have shown previously that BAMBI links inflammation and liver fibrosis via TLR4-dependent modification of TGF-␤ signaling in HSC.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial lipopolysaccharide is a well-known fibrosis-promoting agent by the activation of Toll-like receptor (TLR) 4 signaling, which is expressed on macrophages and HSCs (33,34). In contrast, Kupffer cell activity increases the activity of nuclear factor-kappa β, which in turn promotes pro-inflammatory cytokine secretion (35).…”
Section: Cellular and Physiological Events In Liver Fibrosismentioning
confidence: 99%
“…We previously reported that macrophages underwent apoptosis in dimethylnitrosamineinduced liver fibrosis (Liu et al, 2010). Therefore, in this study, we investigated if macrophages underwent apoptosis in the kidneys during liver cirrhosis.…”
Section: Discussionmentioning
confidence: 93%
“…Macrophages are known to play an important role in liver fibrosis and cirrhosis (Heinrichs et al, 2011;Zimmermann et al, 2011;Heymann et al, 2012;Ramachandran et al, 2012), which is a central component of the final, common pathway leading to HSC activation and ECM deposition (Liu et al, 2008(Liu et al, , 2010Chiu et al, 2014). However, the macrophage in kidneys with cirrhosis has not been well studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation